Comparing Wealth - Data Quality of the HFCS - Anita Tiefensee; Markus M. Grabka (Survey Research Methods, 2016)
The Household Finance and Consumption Survey (HFCS) provides information about house-hold wealth (real and financial assets as well as liabilities) from 15 Euro-countries around the year 2010 (first wave). The survey will be the central dataset in this topic in the future. However, several aspects point to potential methodological constraints regarding cross-country comparability. Therefore the aim of this paper is to get a better insight in the data quality of this important data source. The framework for our analysis is the “Guidelines for Micro Statistics on Household Wealth” from the OECD (2013). We have two main focuses: First, we present a synopsis of cross-country differences, which is the core of the paper. We compare the sampling processes, the interview modes, the oversampling techniques, the unit and item non-response rates and how it is dealt with them via weighting and imputation as well as further points which might restrict cross-country comparability of net wealth. We classify the individual country behavior and evaluate the impact on net wealth. Second, we give a first insight in the selectivity of item non-response in a cross-national setting. We make use of logit models to identify differences in characteristics as well as item non-response patterns across countries. - See more at: https://ojs.ub.uni-konstanz.de/srm/article/view/6305#sthash.ZQboxFMp.dpuf
Keywords: D31; N30; C83; 330; Household Finance and Consumption Survey (HFCS); Data quality; Cross-country comparibilty; Wealth; Item non-response